Peran Tradisi Badabus dalam Menyampaikan Ajaran Islam di Kota Tidore Kepulauan Provinsi Maluku Utara - Puput Aulia Toloa; Chairiawaty; Muhammad Fauzi Arif (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. The Badabus tradition is a unique cultural and religious practice in Tidore Islands City, North Maluku, Indonesia. This tradition is an expression of Islam that combines religious rituals with cultural practices. Tradition and culture play a very important role in the lives of communities. This research aims to understand the social roles conveyed in the Badabus tradition, to understand the role of Islamic education, and the challenges in conveying Islamic teachings through the Badabus tradition in Tidore Islands City. The Badabus tradition in Tidore Islands City, North Maluku, has a significant social role in introducing unity, solidarity, and social conditions among community members. This tradition also plays an important role in introducing education and Islamic values among community members. However, this tradition faces several challenges, such as limitations in human resources, infrastructure, and funding, as well as the threats of modernization and urbanization which can lead to a decline in the number of participants and the loss of cultural heritage. Abstrak. Tradisi Badabus adalah praktik budaya dan keagamaan yang unik di Kota Tidore Kepulauan, Maluku Utara, Indonesia. Tradisi ini merupakan bentuk ekspresi Islam yang menggabungkan ritual keagamaan dengan praktik budaya. Tradisi dan budaya memainkan peran yang sangat penting dalam kehidupan masyarakat. Penelitian ini bertujuan untuk mengetahui peran sosial yang disampaikan dalam tradisi badabus, mengetahui peran edukasi islam, dan tantangan dalam menyampaikan ajaran islam melalui tradisi Badabus di Kota Tidore Kepulauan. Tradisi Badabus di Kota Tidore Kepulauan, Maluku Utara, memiliki peran sosial yang signifikan dalam memperkenalkan persatuan, solidaritas, dan keadaan sosial di antara anggota komunitas. Tradisi ini juga memainkan peran penting dalam memperkenalkan pendidikan dan nilai-nilai Islam diantara anggota komunitas. Namun, tradisi ini menghadapi beberapa tantangan, seperti keterbatasan sumber daya manusia, infrastruktur, dan pendanaan, serta ancaman modernisasi dan urbanisasi yang dapat menyebabkan penurunan jumlah peserta dan hilangnya warisan budaya.